2016
DOI: 10.1128/msphere.00194-16
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Pyrithione Improves the Antibacterial Activity of Silver Sulfadiazine Ointment

Abstract: Topical antimicrobial ointments ostensibly mitigate bacterial wound disease and reliance on systemic antibiotics. Yet studies have called into question the therapeutic benefits of several traditional topical antibacterials, accentuating the need for improved next-generation antimicrobial ointments. Yet the development of such agents consisting of a new chemical entity is a time-consuming and expensive proposition. Considering that drug combinations are a mainstay therapeutic strategy for the treatment of other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Zinc pyrithione is an antiseborrheic, often used in topical formulations, that has previously been shown to have bacteriostatic properties against streptococci and staphylococci, as well as broad-spectrum antimicrobial activity against other Grampositive bacteria, Gram-negative bacteria, and fungi (37,38). The use of zinc pyrithione has been gaining momentum, as evidenced by recent reports of its activity against biofilms (39), aminoglycoside resistance (40), and clearance of bacteria from wound sites (37). Mechanistic studies revealed that membrane permeability is increased in zinc pyrithione-treated cells and may also mediate the influx of damaging metal ions into the cell (38,41).…”
Section: Resultsmentioning
confidence: 99%
“…Zinc pyrithione is an antiseborrheic, often used in topical formulations, that has previously been shown to have bacteriostatic properties against streptococci and staphylococci, as well as broad-spectrum antimicrobial activity against other Grampositive bacteria, Gram-negative bacteria, and fungi (37,38). The use of zinc pyrithione has been gaining momentum, as evidenced by recent reports of its activity against biofilms (39), aminoglycoside resistance (40), and clearance of bacteria from wound sites (37). Mechanistic studies revealed that membrane permeability is increased in zinc pyrithione-treated cells and may also mediate the influx of damaging metal ions into the cell (38,41).…”
Section: Resultsmentioning
confidence: 99%
“…The potential savings of the antimicrobial additive zinc pyrithione were examined within the range recommended for coatings [56,59] and below, i.e., at 0.1% to 0.3%. Table 11 indicates that the amount of additives in the LM latex (in contrast to L0) can be reduced by one-third or more without losing the microbicidal efficiency against the bacterial cultures tested.…”
Section: Antimicrobial Efficiency Of the Paint Filmsmentioning
confidence: 99%
“…Ketoconazole and ciclopirox are the marketed active antifungal ingredients for the pharmaceutical shampoos Ketomed ® and Sebiprox ® respectively, which are prescribed for severe dandruff and seborrhoeic dermatitis. Although Malassezia fungi are the primary target in the over‐the‐counter anti‐dandruff shampoo Head and Shoulders ® (H&S), zinc pyrithione is also known to have broad‐spectrum antimicrobial activity by inhibiting copper influx .…”
Section: Introductionmentioning
confidence: 99%